Contralateral approach using microscope and tubular retractor system for ipsilateral decompression of lumbar degenerative lateral recess stenosis associated with narrow spinal canal - Shu, Longfei; Mu, Qingchun; Dai, Feihu; Zhao, Wei; Syeda, Madiha Zahra; Wang, Yuhai (Frontiers in Neurology, 2024)
Objective To summarize the clinical effect of a single-center retrospective analysis of the contralateral approach with a microscope and tubular retractor system for ipsilateral decompression in patients with lumbar lateral recess stenosis and a narrow spinal canal. Methods A total of 25 patients who underwent ipsilateral decompression surgery via a contralateral approach with microscope and tubular retractor system, performed by one surgeon at a single center were retrospectively examined. The width of the lamina fenestration was compared with the preoperative distance from the root of the spinous process to the dorsal articular facet, the bilateral articular facet change in the suprapedicle notch section on CT scan, and with the changes in transverse and sagittal diameters of the canal area on MRI. Clinical efficacy was assessed using the Japanese Orthopedic Association (JOA), Visual Analog Scale (VAS), and Oswestry Disability Index (ODI) scores. Results In total, 25 patients were treated and the mean intraoperative time was 82.04 ± 12.48 min. There was no nerve injury, cerebrospinal fluid leakage, and infection complications. The postoperative CT revealed that the width of the contralateral laminar fenestration was less than the distance from the root of the spinous process to the dorsal articular facet. The residual widths of the ipsilateral articular facet and contralateral articular facet were greater than 2/3 of the preoperative articular facet width. The transverse and sagittal diameter of canal were significantly increased. The mean follow-up period was 12–16 months, and no recurrence or reoperation incidence were found at the last follow-up. When compared to pre-surgery, the ODI, VAS, and JOA scores were significantly improved after surgery (p < 0.05). Conclusion Based on our single-center retrospective observation of 25 cases and combined with previous literature, the contralateral approach with a microscope and tubular retractor system for ipsilateral decompression in patients with lumbar lateral recess stenosis and a narrow spinal canal can reduce damage to the articular processes, and probably more conducive to the postoperative stability of the lumbar spine. This was a single center retrospective analysis with a small sample size and lacked randomized controlled trials (RCTs). However, larger-scale, multicenter RTCs are required for additional validation.